In The Shadows: Conservative Epistemology and Ideological Value. (August 2022) - Blackburn, Dean
This article intervenes in the debate about the nature of conservatism. Some contributors to this debate have claimed that this ideology can be defined as an adjectival disposition. They claim, that is, that a conservative possesses an attitude towards shared values rather than a distinct set of substantive values. The following discussion interrogates this account of conservatism and concludes that it can only be coherent if we ignore the epistemological limits of conservative thinking.